Yu-gi-oh! GX. Vol. 3, Let the tournament begin!! - Kageyama, Naoyuki (Shonen Jump manga., 2009)
"The Duel Academy Tournament moves into high gear as Jaden and his friends battle it out with each other for a chance to duel the legendary Zane 'Kaiser' Truesdale. American duelists David Rabb and Reggie Mackenzie are also in the running, but their goal is not to take the title of Duel Champion-- They're after nothing less than Winged Kuriboh, Jaden's most trusted, and enchanted, card!"--P. [4] of cover.